1990
DOI: 10.1111/j.1432-1033.1990.tb19408.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbyl free radical as a reliable indicator of free‐radical‐mediated myocardial ischemic and post‐ischemic injury

Abstract: The real-time kinetics of the release of ascorbyl free radicals in the coronary perfusate from isolated rat hearts submitted to an ischemia/reperfusion sequence has been achieved by continuous-flow ESR using high-speed acquisition techniques. Enhanced ESR detection of ascorbyl free radicals was obtained by addition of dimethyl sulfoxide (Me,SO), a strong cation chelator and oxidizing agent. A continuous-flow device allowed a direct monitoring of the ascorbyl free radical and/or ascorbate leakage in coronary pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Thawed samples were quickly introduced into a standard aqueous flat cell which was fitted within the cavity of a Bruker ESP 300 (Karlsruhe, Germany) X-band (9.8 GHz) ESR spectrometer equipped with a TM110 cavity and operating at a field modulation of 100-kHz and a microwave power of 10 mW. Spectral acquisition was initiated at room temperature 60 s after either the addition of DMSO or the complete thawing of the DEPMPO- was performed according to the literature (16,42,44). Free-radical concentrations were derived from double integrals of the simulated spectra obtained with either WinSim software (13) or the program of Rockenbauer and Korecz (48).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thawed samples were quickly introduced into a standard aqueous flat cell which was fitted within the cavity of a Bruker ESP 300 (Karlsruhe, Germany) X-band (9.8 GHz) ESR spectrometer equipped with a TM110 cavity and operating at a field modulation of 100-kHz and a microwave power of 10 mW. Spectral acquisition was initiated at room temperature 60 s after either the addition of DMSO or the complete thawing of the DEPMPO- was performed according to the literature (16,42,44). Free-radical concentrations were derived from double integrals of the simulated spectra obtained with either WinSim software (13) or the program of Rockenbauer and Korecz (48).…”
Section: Methodsmentioning
confidence: 99%
“…6A and B). We have previously shown that the concentration of this AFR-DMSO complex is representative of the ascorbate content of the plasma (42,44). In untreated WT mice, the baseline AFR-DMSO concentration corresponded to the signal yielded by 40 to 50 M sodium ascorbate (Fig.…”
mentioning
confidence: 99%
“…For measurements of Asc  production in the autoxidized Hb solution, an ESR method described by Pietri et al 18) was modiˆed. 14) Brie‰y, Hb (25 mg W ml) autoxidized in PBS was mixed with 1 mM ascorbate.…”
Section: Methodsmentioning
confidence: 99%
“…Production of Asc  as a measure of Hb-catalyzed monoamine radical formation Addition of monoamines to Hb solution containing 2 mM ascorbate and 1 mM H 2 O 2 induced an ESR spectrum with a characteristic doublet signal of Asc  (hyperˆne splitting constant=0.188 mT, g value= 2.005), 18,19) but no signal of Asc  was detected in the absence of ascorbate (Fig. 4).…”
Section: Sion In Omentioning
confidence: 99%
“…It is possible that ascorbyl radical generation occurred secondarily to oxygen-derived freeradical-induced cellular damage (Pietri et al, 1990).…”
Section: Measurement Of Free Radicals In Surgically Induced Lymphedemamentioning
confidence: 99%